Estimation of potassium levels in hemodialysis patients by T wave nonlinear dynamics and morphology markers. (April 2022) - Bukhari, Hassaan A.; Sánchez, Carlos; Srinivasan, Sabarathinam; Palmieri, Flavio; Potse, Mark; Laguna, Pablo; Pueyo, Esther
Abstract: Objective: Noninvasive screening of hypo- and hyperkalemia can prevent fatal arrhythmia in end-stage renal disease (ESRD) patients, but current methods for monitoring of serum potassium ( K + ) have important limitations. We investigated changes in nonlinear dynamics and morphology of the T wave in the electrocardiogram (ECG) of ESRD patients during hemodialysis (HD), assessing their relationship with K + and designing a K + estimator. Methods: ECG recordings from twenty-nine ESRD patients undergoing HD were processed. T waves in 2-min windows were extracted at each hour during an HD session as well as at 48 h after HD start. T wave nonlinear dynamics were characterized by two indices related to the maximum Lyapunov exponent (λ t, λ wt ) and a divergence-related index ( η ). Morphological variability in the T wave was evaluated by three time warping-based indices (dw, reflecting morphological variability in the time domain, and da and d a NL, in the amplitude domain). K + was measured from blood samples extracted during and after HD. Stage-specific and patient-specific K + estimators were built based on the quantified indices and leave-one-out cross-validation was performed separately for each of the estimators. Results: The analyzed indices showed high inter-individual variability in their relationship with K + . Nevertheless, all of them had higher values at the HD start and 48 h after it, corresponding to the highest K + . The indices η and dw were the most strongly correlated with K + (median Pearson correlation coefficient of 0.78 and 0.83, respectively) and were used in univariable and multivariable linear K + estimators. Agreement between actual and estimated K + was confirmed, with averaged errors over patients and time points being 0.000 ± 0.875 mM and 0.046 ± 0.690 mM for stage-specific and patient-specific multivariable K + estimators, respectively. Conclusion: ECG descriptors of T wave nonlinear dynamics and morphological variability allow noninvasive monitoring of K + in ESRD patients. Significance: ECG markers have the potential to be used for hypo- and hyperkalemia screening in ESRD patients. Highlights: ECG markers of T wave nonlinear dynamics highly correlate with serum potassium. T wave nonlinear dynamics are complementary to T wave morphology descriptors. Accurate estimation of serum potassium by T wave nonlinear dynamics and morphology. Current ECG-based methods for hyperkalemia monitoring in ESRD are improved.